Optimalisasi Gizi Ibu Hamil Di Era Stunting: Edukasi Konsumsi Ikan Lele (Clarias Sp.) Sebagai Sumber Protein Hewani Terjangkau Pada Komunitas Posyandu - Welly Handayani; Novia Rita Aninora; Putri Permata Sari; Nela Novita Sari (-, 2026)
The stunting rate in Indonesia remains a serious national nutritional concern, with one of its key determinants being insufficient animal protein intake among pregnant women. Catfish (Clarias sp.) is a local fishery commodity rich in protein, omega-3 fatty acids, iron, and calcium, yet its utilization by pregnant women remains suboptimal due to limited nutritional knowledge. This community service activity aimed to enhance the knowledge and awareness of pregnant women regarding the benefits of catfish consumption as an affordable source of animal protein to support fetal health and prevent stunting. Methods included interactive counseling, catfish cooking demonstrations, and distribution of educational leaflets at Jorong Pulau Air, Kanagarian Pulau Air Nan Sabaris, Padang Pariaman Regency, involving 32 pregnant women in trimesters I–III. Results showed a statistically significant improvement in nutritional knowledge (pre-test mean 52.3 increased to post-test mean 81.7 out of 100) and an increased willingness to regularly consume catfish. This activity is expected to serve as a community-based nutritional education model replicable in other regions to support the national program for stunting reduction.